(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2018)
The ability of anguish to reveal the hidden is, evidently, in relation to the essential uncovering activity of Dasein. This proposal continues the transcendental perspective of phenomenology even from the Heidegger’s hermeneutic renewal. Anguish could be a pre-theoretical way of reduction; what we will call here ontological reduction. In this way, the anguish puts in value the affective dispositions in the project of thinking something which, until now, has not been thought.